1996
DOI: 10.1128/jcm.34.12.3072-3074.1996
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PCR inhibitors in cervical specimens by using the AMPLICOR Chlamydia trachomatis assay

Abstract: To determine the susceptibility of AMPLICOR Chlamydia trachomatis PCR to inhibitory factors possibly present in cervical specimens, we obtained cervical specimens from 200 gynecology patients attending our outpatient clinic. The prevalence of C. trachomatis infection was 4.1%, as determined by cell culture. All AMPLICOR specimens were tested in one procedure as described by the manufacturer, and after the specimen was spiked with C. trachomatis, several other pretreatment protocols were used. Complete inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
1
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 9 publications
4
45
1
1
Order By: Relevance
“…This value is of the same order of magnitude as that reported by others for inhibition in urine specimens (2.6 and 1.8%) for amplified testing (3,15). Most investigators now believe that inhibitors to amplification exist for both urine and cervical specimens (3,15,35). A combination of heat treatment (95°C for 10 min) and 10-fold dilution of the processed specimen reduced inhibition of PCR from 19 to 4% in one study (35).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This value is of the same order of magnitude as that reported by others for inhibition in urine specimens (2.6 and 1.8%) for amplified testing (3,15). Most investigators now believe that inhibitors to amplification exist for both urine and cervical specimens (3,15,35). A combination of heat treatment (95°C for 10 min) and 10-fold dilution of the processed specimen reduced inhibition of PCR from 19 to 4% in one study (35).…”
Section: Discussionsupporting
confidence: 75%
“…It is possible that freezing and thawing of these processed urine specimens reduced or destroyed some LCR inhibitors. Freezing and thawing reduced the inhibition from 19 to 16% in one study (35). Additionally, the experiment which tested the archived urine of 65 pregnant women demonstrated only three (4.6%) inhibited specimens.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also the correct amplification procedure should be proven for every individual PCR tube as PCR inhibition can occur. 16,17 This can easily be accomplished with internal controls. Internal controls, or mimics, contain the same primer sequences as the target, but a different intermediate sequence and can thus be differentiated from the target.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of the PCR process have been described in cervical specimens at a frequency of 19% by Verkooyen et al, 28 using the method of detection we used. Using more sophisticated methods, Bass et al 20 found inhibitors in 4% of their specimens.…”
Section: Discussionmentioning
confidence: 99%